TANGGUNG JAWAB GANTI RUGI ATAS PEMUTUSAN KONTRAK KERJA SEPIHAK TERHADAP PEKERJA OLEH PT.SUCOFINDO EPISI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - ERIZA, NOVI; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Article 62 of the Employment Act has stated that, If one of the parties terminate the employment relationship prematurely ended or before the work packages of certain specified in the agreement is completed or terminates the employment relationship not because the worker died, and not because the end of the employment agreement, is obliged to pay wages workers until the expiry time for a period of employment agreement.The reality on the PT. Sucofindo Episi had terminate employment before the contract expires and the company does not want to pay in full the remainder of the contract is still there, as a result of workers suffered a loss in addition to not work anymore, workers' rights have not been fully met.Keyword: Torts - Employment Contracts - Termination